Answer:
there’s no photo
Step-by-step explanation:
That’s a lot of money. that’s literally $5,550 a day
Using an exponential function, it is found that:
- For Country A, the doubling time is of 43 years.
- For Country B, the growth rate is of 1.9% per year.
<h3>What is the exponential function for population growth?</h3>
The exponential function for population growth is given as follows:
![P(t) = P(0)e^{kt}](https://tex.z-dn.net/?f=P%28t%29%20%3D%20P%280%29e%5E%7Bkt%7D)
In which:
- P(t) is the population after t years.
- P(0) is the initial population.
- k is the exponential growth rate, as a decimal.
For Country A, we have that k = 0.016. The doubling time is t for which P(t) = 2P(0), hence:
![P(t) = P(0)e^{kt}](https://tex.z-dn.net/?f=P%28t%29%20%3D%20P%280%29e%5E%7Bkt%7D)
![2P(0) = P(0)e^{0.016t}](https://tex.z-dn.net/?f=2P%280%29%20%3D%20P%280%29e%5E%7B0.016t%7D)
![e^{0.016t} = 2](https://tex.z-dn.net/?f=e%5E%7B0.016t%7D%20%3D%202)
![\ln{e^{0.016t}} = \ln{2}](https://tex.z-dn.net/?f=%5Cln%7Be%5E%7B0.016t%7D%7D%20%3D%20%5Cln%7B2%7D)
![0.016t = \ln{2}](https://tex.z-dn.net/?f=0.016t%20%3D%20%5Cln%7B2%7D)
![t = \frac{\ln{2}}{0.016}](https://tex.z-dn.net/?f=t%20%3D%20%5Cfrac%7B%5Cln%7B2%7D%7D%7B0.016%7D)
t = 43 years.
For Country B, P(36) = 2P(0), hence we have to solve for k to find the growth rate.
![P(t) = P(0)e^{kt}](https://tex.z-dn.net/?f=P%28t%29%20%3D%20P%280%29e%5E%7Bkt%7D)
![2P(0) = P(0)e^{36k}](https://tex.z-dn.net/?f=2P%280%29%20%3D%20P%280%29e%5E%7B36k%7D)
![e^{36k} = 2](https://tex.z-dn.net/?f=e%5E%7B36k%7D%20%3D%202)
![\ln{e^{36k}} = \ln{2}](https://tex.z-dn.net/?f=%5Cln%7Be%5E%7B36k%7D%7D%20%3D%20%5Cln%7B2%7D)
![36k = \ln{2}](https://tex.z-dn.net/?f=36k%20%3D%20%5Cln%7B2%7D)
![k = \frac{\ln{2}}{36}](https://tex.z-dn.net/?f=k%20%3D%20%5Cfrac%7B%5Cln%7B2%7D%7D%7B36%7D)
k = 0.019.
For Country B, the growth rate is of 1.9% per year.
More can be learned about exponential functions at brainly.com/question/25537936
#SPJ1
Answer:
C) 4
Step-by-step explanation:
Arcs on one side of the diameter adds upto 180°.
Therefore,
![(2 + 17x) \degree + 54 \degree + 56 \degree = 180 \degree \\ \\ (2 + 17x) \degree + 110 \degree = 180 \degree \\ \\ (2+ 17x) \degree = 180 \degree - 110 \degree\\ \\ (2 + 17x) \degree = 70 \degree \\ \\ 2 + 17x = 70 \\ 17x = 70 - 2 \\ \\ x = \frac{68}{17} \\ \\ x = 4](https://tex.z-dn.net/?f=%282%20%2B%2017x%29%20%5Cdegree%20%2B%2054%20%5Cdegree%20%2B%2056%20%5Cdegree%20%3D%20180%20%5Cdegree%20%5C%5C%20%20%5C%5C%20%282%20%2B%2017x%29%20%5Cdegree%20%2B%20110%20%5Cdegree%20%20%3D%20180%20%5Cdegree%20%5C%5C%20%20%5C%5C%20%282%2B%2017x%29%20%5Cdegree%20%3D%20180%20%5Cdegree%20%20-%20110%20%5Cdegree%5C%5C%20%20%5C%5C%20%20%282%20%2B%2017x%29%20%5Cdegree%20%3D%2070%20%5Cdegree%20%20%5C%5C%20%20%5C%5C%202%20%2B%2017x%20%3D%2070%20%5C%5C%2017x%20%3D%2070%20-%202%20%5C%5C%20%20%5C%5C%20x%20%3D%20%20%5Cfrac%7B68%7D%7B17%7D%20%20%5C%5C%20%20%5C%5C%20x%20%3D%204)